Identifying Needs of Food Composition Database Users – PortFIR experience - Dias, M. Graça (2014)
Information sharing and management among all the intervenients in food chain is crucial to improve food safety and to promote and protect public health. It optimizes resources usage and provides evidence support to define and promote policies in food and nutrition and to increase the efficiency of food productive systems. Objectives. To share information among Portuguese Food Composition Table users, to identify their needs, in order to define priorities for the update of the National Food Composition Table. Material and Methods. INSA, IP established a partnership with GS1 Portugal, to develop a programme, “Portuguese Food Information Resource” (PortFIR), to implement national networks of knowledge sharing on nutrition and food safety. The program has the collaboration of governmental and private organizations encompassing health, agriculture and economy sectors and includes a food information web portal integrated in a Food Information Network Management System (SGRIA). Two networks were created to date, “Food Composition” and “Food Microbiological Information”, acting through working groups (WG), some of which are transversal to both networks. “Users” WG (GTU) developed a questionnaire to evaluate the needs and satisfaction of the users of the Portuguese Food Composition Table (FCT). The questionnaire was implemented on-line from July to October 2011 using the software LimeSurvey®, and FCT users were invited to participate through direct contact by email and/or through professional associations and networks. Results. The analysis of the responses revealed that the preferred format of the FCT is “on-line” (52%) (options: on-line, CD-Rom, book, other) and that 80% of responding users are satisfied with either FCT format. Regarding additional information needs, users refer allergens (50%), food portion (39%), fatty acids n-3 and n-6 (25%), and traditional dishes (23%). Respondents consider the number of foods, micronutrients and composite dishes as the main limitations of the present FCT. Conclusions. The cooperation between data producers, users and compilers is contributing to optimize the usage of National resources and to disseminate the knowledge about nutrition and food safety within the country. The information obtained through “PortFIR – GTU” will allow compilers to establish informed priorities taking into account the expressed needs of users across the food chain.